CONNOTATIVE AND DENOTATIVE MEANING OF ADELE'S SONG LYRICS “EASY ON ME” - Wawat Srinawati (Journal Fascho in Education Conference-Proceedings, 2021)
There are different types of meaning in language, one of the branches of linguistics that deals with meaning is semantics. Semantics is known as the study of meaning. This study aims to analyze the connotative and denotative meanings contained in song lyrics, expressions of feelings or ideas usually expressed through song lyrics. The song selected for this research data is Adele's song, entitled "Easy On Me". The analysis used is a descriptive qualitative method that aims to analyze everyday phenomena and analyze the use of words, including finding the meaning contained in song lyrics. The results of the analysis of connotative meanings are more than denotative meanings in Adele's song lyrics. The number of connotative meanings and denotative meanings are not much different, but the connotative meanings are more because this song has many meanings that actually don't exist.